Monetarism rides again? US monetary policy in a world of Quantitative Easing - Vo Phuong Mai Le; David Meenagh; Patrick Minford (Cardiff University, Cardiff Business School, 2014)
This paper gives money a role in providing cheap collateral in a model of banking; besides the Taylor Rule, monetary policy can affect the risk-premium on bank lending to firms by varying the supply of M0, so at the zero bound monetary policy is effective; fiscal policy crowds out investment via the risk-premium. A rule for making M0 respond to credit conditions can enhance the economy's stability. Both price-level and nominal GDP targeting rules for interest rates combined with this stabilise the economy further. With these rules for monetary control, aggressive and distortionary regulation of banks' balance sheets becomes redundant.
Keywords: E3; E44; E52; C1; 330; DSGE model; Financial Frictions; Crises; Indirect Inference; money supply; QE; monetary policy; fiscal multiplier; zero bound